TRANSFORMATION OF CHARACTER EDUCATION IN INDONESIA; SYNERGY BETWEEN THE CURRICULUM AND PANCASILA VALUES: " Sinergi Antara Kurikulum Dan Nilai-Nilai Pancasila" - Juita, Jihan (JURNAL SETIA PANCASILA, 2025)
Character education in Indonesia is an important strategic step in creating a young generation that not only excels academically, but also has good morals and ethics. Based on Pancasila, character education must be integrated into all aspects of education, involving educational institutions, parents, communities and graduates. Cooperation between all levels of society is essential to create an atmosphere conducive to the teaching of character values such as tolerance, empathy and honesty. In addition, the use of information technology and government policy support to integrate character education into the curriculum are also very important. Through this comprehensive approach, it is hoped that Indonesia's young generation can become leaders with integrity who are able to face global challenges and make a positive contribution to the nation's progress. Integrating Pancasila values necessity to create a civilised, ethical and highly competitive society.